Hubungan Parasocial Relationship dan Kesepian pada Remaja Penggemar K-Pop - Simanjaya, Clarissa Chrishella; Subroto, Untung (Lembaga Yasin AlSys, 2025)
The phenomenon of Korean Pop (K-Pop) has become an important part of global popular culture and is highly favored by Indonesian adolescents, such that fans’ emotional involvement with their idols often forms one-way or parasocial relationships that may be associated with feelings of loneliness. This study aimed to examine the relationship between parasocial relationships and the level of loneliness among adolescent K-Pop fans. A quantitative approach was employed with 207 adolescents aged 15–19 years who were active K-Pop fans and had been part of a fandom for at least six months. The instruments used were the Celebrity Attitude Scale (CAS) to measure parasocial relationships and the UCLA Loneliness Scale Version 3 to measure loneliness. Data were analyzed using Spearman’s correlation. The results showed a significant but weak positive relationship between parasocial relationships and loneliness among adolescent K-Pop fans, with a correlation coefficient of rₛ = 0.316 and a significance value of p = 0.000 (p < 0.01). These findings indicate that the higher the level of adolescents’ parasocial relationships with K-Pop idols, the higher the level of loneliness they experience, thereby providing important implications for parents, educators, and mental health practitioners to pay closer attention to the dynamics of parasocial relationships in the context of adolescents’ use of digital entertainment media.